Diarrhoeal Diseases in Developing Countries: A Situational Analysis - Kumar, SG; Subita, L (Kathmandu University Medical Journal, 2013)
Recent data showed that there is no much reduction in diarrhoea related morbidity in developing countries. This is important in view of the Millennium Developmental Goal (MDG) to be achieved by 2015. This study reviewed and analyzed after gathering the recent literature information from Pubmed, internet and other sources. The authors discussed public health issues related to diarrhoeal diseases that include problem burden, determinants, intervention strategies, management, prevention and recent developments for control of diarrhoea among under-five children in developing countries. The study emphasizes the need for strengthening of comprehensive diarrhoeal disease prevention strategy at primary level including improvement of water quality, hygiene and sanitation, along with provision of oral rehydration solution and zinc supplements, and research in the field of vaccine and cost effective interventions. Kathmandu University Medical Journal | Vol.10 | No. 2 | Issue 38 | Apr – June 2012 | Page 83-88 DOI: http://dx.doi.org/10.3126/kumj.v10i2.7351